Blastic plasmacytoid dendritic cell neoplasm with absolute monocytosis at presentation - Jaworski JM; Swami VK; Heintzelman RC; Cusack CA; Chung CL; Peck J; Fanelli M; Styler M; Rizk S; Hou JS (Dove Medical Press, 2015)
Joseph M Jaworski,1,2 Vanlila K Swami,1 Rebecca C Heintzelman,1 Carrie A Cusack,3 Christina L Chung,3 Jeremy Peck,3 Matthew Fanelli,3 Micheal Styler,4 Sanaa Rizk,4 J Steve Hou1 1Department of Pathology and Laboratory Medicine, Hahnemann University Hospital/Drexel University College of Medicine, Philadelphia, PA, USA; 2Department of Pathology, Mercy Fitzgerald Hospital, Darby, PA, USA; 3Department of Dermatology, Hahnemann University Hospital/Drexel University College of Medicine, Philadelphia, PA, USA; 4Department of Hematology/Oncology, Hahnemann University Hospital/Drexel University College of Medicine, Philadelphia, PA, USA Abstract: Blastic plasmacytoid dendritic cell neoplasm is an uncommon malignancy derived from precursors of plasmacytoid dendritic cells. Nearly all patients present initially with cutaneous manifestations, with many having extracutaneous disease additionally. While response to chemotherapy initially is effective, relapse occurs in most, with a leukemic phase ultimately developing. The prognosis is dismal. While most of the clinical and pathologic features are well described, the association and possible prognostic significance between peripheral blood absolute monocytosis (>1.0 K/µL) and blastic plasmacytoid dendritic cell neoplasm have not been reported. We report a case of a 68-year-old man who presented with a rash for 4–5 months. On physical examination, there were multiple, dull-pink, indurated plaques on the trunk and extremities. Complete blood count revealed thrombocytopenia, absolute monocytosis of 1.7 K/µL, and a negative flow cytometry study. Biopsy of an abdominal lesion revealed typical features of blastic plasmacytoid dendritic cell neoplasm. Patients having both hematologic and nonhematologic malignancies have an increased incidence of absolute monocytosis. Recent studies examining Hodgkin and non-Hodgkin lymphoma patients have suggested that this is a negative prognostic factor. The association between blastic plasmacytoid dendritic cell neoplasm and absolute monocytosis has not been described and may, in fact, have prognostic value. Keywords: blastic, plasmacytoid, dendritic, monocytosis